Evaluation of Maxillary Impacted Teeth and Their Relationship with Adjacent Teeth and Anatomic Structures with Cone Beam Computed Tomography - Canger, Emin Murat; Köse, Emre (Journal of Dentistry Indonesia, 2020)
Objective: This study aimed to examine the cone beam computed tomography (CBCT) images of impacted maxillary canines and mesiodentes. Methods: This retrospective radiographic study was performed on 177 patients with 200 impacted maxillary canines and 12 mesiodentes. Using CBCT images, the unilateral/bilateral occurrence, presence of root dilaceration, mesio-distal and buccopalatal location, impaction condition, contact region of adjacent teeth, presence and degree of root resorption of adjacent teeth, dental follicle width, closest distance to the nasal cavity, nasopalatinal canal, and maxillary sinus were assessed. For mesiodentes, the types, follicle width, direction, and relationship with anatomical structures were evaluated. Results: No statistical relationship was found between (buccopalatal and mesio-distal) position of canine and root resorption of adjacent teeth (p = 0.171). A negative correlation was observed between age and follicle width (r = −0.145, p = 0.048). No mesiodens with enlarged follicle and root resorption of adjacent teeth was found. Conclusion: Given the negative correlation between age and follicle width, older patients with impacted teeth can be followed up by two-dimensional radiographs unless periradicular radiolucencies are absent. Otherwise, CBCT evaluation is required for early detection of pathologies and prevention of possible surgical complications.